Improved survival of locoregional-advanced larynx and hypopharynx cancer patients treated according to the DeLOS-II protocol - Wichmann, Gunnar; Wald, Theresa; Pirlich, Markus; Stoehr, Matthaeus; Zebralla, Veit; Kuhnt, Thomas; Nicolay, Nils Henrik; Hambsch, Peter; Krücken, Irene; Hoffmann, Karl-Titus; Lordick, Florian; Kluge, Regine; et al. (Frontiers in Oncology, 2024)
Introduction Larynx organ preservation (LOP) in locoregional advanced laryngeal and hypopharyngeal squamous cell carcinoma (LA-LHSCC) being only R0-resectable (clear margins > 5 mm) by total laryngectomy (TL) is desirable. Based on tumor-specific (TSS) and overall survival (OS) data from the RTOG 91-11 trial and meta-analyses of randomized clinical trials (RCT), cisplatin-based concurrent radio-chemotherapy (CRT) is discussed being superior to cisplatin-based induction-chemotherapy followed by radiotherapy (IC+RT) and TL followed by postoperative RT (TL+PORT) or radiochemotherapy (TL+PORCT). Outside of RCTs, T4 LHSCC treated with TL+PORCT demonstrated improved OS and TSS compared to CRT alone; comparisons with docetaxel plus cisplatin (TP) -based IC+RT are unpublished. Head-to-head comparisons in RCTs of these 4 alternatives are missing. Material and Methods We utilized monocentric registry data to compare the outcome in the LOP trial DeLOS-II (NCT00508664) and propensity score (PS)-matched LHSCC patients. DeLOS-II utilized endoscopic tumor staging after 1 cycle of TP-based IC for selecting TL+R(C)T for non-responders vs. IC+RT for responders. Main risk factors for survival (localization hypopharynx, T4, N+, tobacco smoking >30 pack years, alcohol consumption >60 g/day, age, sex) were used to calculate the individual PS for each DeLOS-II patient and 330 LHSCC patients suitable for DeLOS-II according to eligibility criteria in Leipzig by CRT (78), TL+PORT (148) and TL+PORCT (104). We performed PSmatching with caliper width 0.2. Results The 52 DeLOS-II patients (whole intent-to-treat cohort) and 3 PS-matched cohorts (52 LHSCC patients each) had equal distribution regarding risk factors including Charlson comorbidity score (CS; all p>0.05) but differed in outcome. During 12,498.6 months of follow-up, 162 deaths (36/41/43/42 in DeLOS-II/ TL+PORCT/ TL+PORT/CRT, p=0.356) occurred; DeLOS-II patients had superior OS and TSS. Compared to DeLOS-II, the HR (95%-CI) observed in TL+PORCT, TL+PORT and CRT for OS and TSS were